Word problems in upper secondary algebra in Sweden over the years 1960–2000 - Jakobsson-Åhl, Teresia (NOMAD Nordic Studies in Mathematics Education, 2008)
This paper reports results from a study on school algebra at the upper secondary level. The study considered changes in the algebraic content as it was presented in mathematics textbooks in the second half of the twentieth century in Sweden. The paper describes the changes of word problems in terms of the way they are used for developing algebraic skills. It is shown in what ways the place of the problems, the context and the use of mathematical models changed in the period in question. The use of word problems is related to the curricular documents of the time and to different views on school algebra.